Negotiation-Collaboration for Quality of Quality Requirements - Linhares, Giovana Brandão Ribeiro; Leite, Julio Cesar (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
In general, Non-Functional Requirements (NFRs) are handled during activities related to software architecture, and often also in implementation. This results in higher costs and low quality softwares. This work studies mechanisms to promote the NFRs from the understanding of human relationships occurring in the collaborative dynamics, permeated by negotiations during the requirements construction activities. A collaborative strategy for the construction of NFRs and their computational support are proposed. To evaluate this research, a qualitative experiment will be carried out in a real organization, in the Telecommunication area.